Efektivitas Media Canva Terhadap Keterampilan Membaca Permulaan Peserta Didik Sekolah Dasar - Sri Ayu Permata Sari; Vevy Liansari (Indonesian Journal Publisher, 2026)
Education plays a crucial role in developing students' basic skills, including early reading skills, which serve as the foundation for elementary school learning. While learning continues, some lower-grade students still experience difficulties in recognizing letters, constructing syllables, and reading simple words and sentences. One way to address this is by utilizing engaging and interactive learning media, such as Canva. This study aimed to determine the effectiveness of Canva in improving elementary school students' early reading skills. This study employed a quantitative approach with a pre-experimental design using a one-group pretest–posttest model. The subjects were 32 first-grade students at Muhammadiyah 1 Elementary School, Sidoarjo. The data collection tool used was an early reading test administered before and after treatment. The data were analyzed using normality tests, homogeneity tests, and paired sample t-tests. The results showed a significant increase in the average score of students' early reading skills after learning using Canva. The t-test results showed a significance value of 0.000 < 0.05, indicating a significant difference between the pretest and posttest results. Therefore, it can be concluded that Canva media is effective in improving elementary school students' beginning reading skills.